Arginine methylation of the DDX5 helicase RGG/RG motif by PRMT5 regulates resolution of RNA:DNA hybrids. (21st June 2019) - Mersaoui, Sofiane Y; Yu, Zhenbao; Coulombe, Yan; Karam, Martin; Busatto, Franciele F; Masson, Jean‐Yves; Richard, Stéphane
Abstract: Aberrant transcription‐associated RNA:DNA hybrid (R‐loop) formation often causes catastrophic conflicts during replication, resulting in DNA double‐strand breaks and genomic instability. Preventing such conflicts requires hybrid dissolution by helicases and/or RNase H. Little is known about how such helicases are regulated. Herein, we identify DDX5, an RGG/RG motif‐containing DEAD‐box family RNA helicase, as crucial player in R‐loop resolution. In vitro, recombinant DDX5 resolves R‐loops in an ATP‐dependent manner, leading to R‐loop degradation by the XRN2 exoribonuclease. DDX5‐deficient cells accumulate R‐loops at loci with propensity to form such structures based on RNA:DNA immunoprecipitation (DRIP)‐qPCR, causing spontaneous DNA double‐strand breaks and hypersensitivity to replication stress. DDX5 associates with XRN2 and resolves R‐loops at transcriptional termination regions downstream of poly(A) sites, to facilitate RNA polymerase II release associated with transcriptional termination. Protein arginine methyltransferase 5 (PRMT5) binds and methylates DDX5 at its RGG/RG motif. This motif is required for DDX5 interaction with XRN2 and repression of cellular R‐loops, but not essential for DDX5 helicase enzymatic activity. PRMT5‐deficient cells accumulate R‐loops, resulting in increased formation of γH2AX foci. Our findings exemplify a mechanism by which an RNA helicase is modulated by arginine methylation to resolve R‐loops, and its potential role in regulating transcription. Synopsis: Association of the helicase DDX5 and the nuclease XRN2 is dependent on PRMT5‐mediated arginine methylation of DDX5 and important for resolution of RNA/DNA hybrids at transcriptional termination regions, implicating this mechanism in XRN2‐mediated transcriptional termination. PRMT5 inhibition leads to R‐loops accumulation and DNA damage. Arginine methylation of the DDX5 RGG/RG motif regulates its association with XRN2 nuclease. DDX5 functions with XRN2 to resolve R‐loops at transcription termination sites. Recombinant DDX5 resolves R‐loops, but not D‐loops, in vitro via its helicase activity. Abstract : Association of DDX5 with XRN2 nuclease controlled by the methyltransferase PRMT5 is important for removing R‐loops at transcriptional termination regions.